Biaxial defect cores in nematic equilibria an asymptotic result - Majumdar, A; Pisante, A; Henao, D (2012)
We analyze nematic defects on arbitrary three-dimensional (3D) geometries subject to strong anchoring boundary conditions, for low temperatures. We obtain a complete characterization of defect profiles in physically realistic uniaxial solutions, in the low-temperature limit. We show that (i) the radial-hedgehog (RH) solution is the only admissible uniaxial defect in the low-temperature limit and (ii) Landau-de Gennes energy minimizers must have biaxial defect cores for low temperatures.